2010
DOI: 10.1016/j.freeradbiomed.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of the mitochondrial complex I subunit NDUFB8 elicits RIP1- and RIP3-mediated necrosis

Abstract: Nitric oxide and other reactive nitrogen species target multiple sites in the mitochondria to impact cellular bioenergetics and survival. Kinetic imaging studies revealed that NO from either activated macrophages or donor compounds rapidly diffuses to the mitochondria, causing a dose dependent progressive increase in NO-dependent DAF fluorescence that corresponded to mitochondrial membrane potential loss, and initiated alterations in cellular bioenergetics that ultimately led to necrotic cell death. Cellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 66 publications
6
75
2
1
Order By: Relevance
“…In addition, we saw that phosphorylation of Rip1 rapidly Upon SM treatment, Rip3 and to a lesser extent Rip1 showed increased expression. Similarly, increased Rip3 expression in necroptotic cells has recently been reported, 38 and analysis of different cell lines has shown that sensitivity to TNF-a/zVAD-FMK-induced necrosis is determined by Rip3 expression. 11 Quantitative RT-PCR revealed that upregulation of Rips following SM treatment is likely post-transcriptional.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, we saw that phosphorylation of Rip1 rapidly Upon SM treatment, Rip3 and to a lesser extent Rip1 showed increased expression. Similarly, increased Rip3 expression in necroptotic cells has recently been reported, 38 and analysis of different cell lines has shown that sensitivity to TNF-a/zVAD-FMK-induced necrosis is determined by Rip3 expression. 11 Quantitative RT-PCR revealed that upregulation of Rips following SM treatment is likely post-transcriptional.…”
Section: Discussionmentioning
confidence: 58%
“…Images were acquired using a Carl Zeiss 510 Meta confocal system with excitation at 488 nm and 561 nm for ROS and ⌬m, respectively. Five images were collected randomly for each sample, and fluorescence change was quantified using Image J software (13,39 and rela Ϫ/Ϫ MEFs with IFN-␥ and monitored cell survival over a period of 72 h. As a positive control, we used TNF-␣, which is known to trigger apoptosis in the absence of RelA (5). As expected, TNF-␣ induced robust cell death of rela Ϫ/Ϫ MEFs within 12 to 24 h of challenge ( Fig.…”
Section: Cells and Reagents Early Passage Relamentioning
confidence: 73%
“…The NDUFB8 subunit is essential for the assembly, structure stability and function of the complex [39,46] and its knockdown decreases complex I activity in animals [10]. We, therefore, reasoned that NDUFB8 deficiency should reflect the entire complex.…”
Section: Discussionmentioning
confidence: 99%
“…Serial 3 μm thick sections were stained with primary antibodies (all from Abcam) against complex I (NDUFB8, ab110242, dilution 1:300), complex II (anti-SDHA, ab14715, dilution 1:4000), complex III (anti-UQCRC2, ab14745, dilution 1:10,000), complex IV (COX-I, ab14705, dilution 1:10,000), complex V (ATP-synthase, ab14748, dilution 1:10,000), and the mitochondrial membrane marker porin (VDAC1, ab14734, dilution 1:10,000). We chose the NDUFB8 subunit because it is central to complex I assembly and function [10,39,46] and has been widely used as a marker of the integrity of the complex [16,40,41]. Sections were deparaffinised in Histoclear and rehydrated in graded ethanol.…”
Section: Immunohistochemistrymentioning
confidence: 99%